An insight into the effects of ratios and temperatures on a Tetrabutylammonium bromide with Ethylene glycol deep eutectic solvent - Yusof, Rizana; Jumbri, Khairulazhar; Abdul Rahman, Mohd Basyaruddin (Elsevier, 2021)
Molecular dynamics (MD) simulations were performed to study the structures and properties of a deep eutectic solvent (DES) synthesised from tetrabutylammonium bromide (TBAB) paired with ethylene glycol (EG). Measurements were performed at different mol ratios of TBAB:EG (1:2 to 1:6) and temperatures (303 to 333 K). Upon validation, MD simulations of DES’s density confirmed results to be in good agreement with previously validated experimental density (Maximum Deviation = 3.91%). The effects of different ratios and temperatures on radial distribution function (RDF), spatial distribution function (SDF), hydrogen bonding, mean square displacement (MSD) and self-diffusion coefficient of the TBAB:EG system were investigated. From RDF analysis, it was observed that Br− moved further away from TBA+ and formed a hydrogen bond with the hydroxyl group (OH) on EG at the closest distance of 0.270 nm. The self-diffusion coefficient of TBA+, Br− and EG increased proportionately to EG. High numbers of hydrogen bonds were observed at a high EG ratio as more intermolecular bondings between EG-Br were established. Hence, the introduction of EG molecules significantly affected ionic interaction within the resulting DES and changed its properties. Experimental data from infrared (IR) spectra and NMR were used to show a correlation between the formation of hydrogen-bonded EG-Br as observed in RDF. Increasing temperatures also altered the RDF, MSD and hydrogen bonding properties of the DES. Meanwhile, the main factor determining ionic movement was found to be the presence of TBA, as the ability of its cation’s long alkyl side chain to form clustering ions dictated the behaviour of the liquid. Therefore, the changes in ratios and temperatures in DESs are essential in predicting their properties and subsequently, in ascertaining the industrial applicability of a particular DES. The presented results showed that the studied DES can be used for many applications and suit the requirement for DNA technology, especially for DNA solvating medium.